Effect of Pets on Human Behavior and Stress in Disaster - Tanaka, Aki; Saeki, Jun; Hayama, Shin-ichi; Kass, Philip H. (Frontiers in Veterinary Science, 2019)
Animal-related consequences were not anticipated in disaster preparedness planning in Japan at the time of its massive earthquakes in 2011. Evacuation failure was quite common due to pet ownership in this disaster. Public attention to the welfare of affected animals in this disaster triggered an awareness of the importance of caring for their needs. However, research on human behavior toward pets or effect of pets on human during disasters remains sparse. In this study, post-traumatic stress disorder (PTSD) scores among pet-owners and non-pet owners in Japan's 2011 earthquake disaster were compared, and attitudes toward pets were evaluated. A questionnaire was distributed to attendees, and interviews were performed at an annual animal welfare event. The Japanese-language version of the revised Impact of Event Scale was used to evaluate PTSD from the disaster. PTSD scores were higher in pet-owners compared to non-pet owners immediately after the earthquakes, but were lower in pet-owners compared to non-pet owners 4.4 years following the disaster. Most people opined that pets should evacuate with people, although less than half of non-pet owners agreed with having animals co-located at evacuation centers. In order to enhance safety and security of both humans and animals at evacuation centers, it is important to proactively address animal issues in disaster preparedness planning. Although pets were regarded by some as adverse risk factors for human health and safety during a disaster; this study instead suggests that pets may play an important positive and protective role for disaster victims.